Terrazzo structure and method for manufacturing terrazzo structure
A terrazzo structure with balanced components of cement, sand, crushed tiles, and pebbles improves mechanical strength and water retention, enabling its use on heavy-traffic surfaces.
Patent Information
- Application Number
- JP2023115949
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-14
AI Technical Summary
Terrazzo surfaces lack sufficient mechanical strength to withstand heavy vehicles and have inadequate water retention properties, leading to issues like cracking and slipping when wet, limiting their outdoor application.
A terrazzo structure composed of specific ratios of cement, pulverized sand, crushed tiles or bricks, and crushed pebbles or ceramics, with controlled particle sizes and water absorption properties, enhancing mechanical strength and water retention.
The terrazzo structure achieves sufficient mechanical strength to support heavy vehicles and maintains water retention, preventing slipping and damage on floors and parking lots.
Smart Images

Figure 2025012822000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a terrazzo structure and a method for manufacturing a terrazzo structure. [Background technology]
[0002] Terrazzo is a type of artificial stone made by mixing aggregates such as crushed stone like marble and granite with cement paste, hardening it, polishing the surface, and grinding the aggregate. Because of its beautiful surface, it is used in lobbies, halls, corridors, school floors, shopping streets, shopping floors in underground malls, concourses in train stations, etc.
[0003] There are two types of terrazzo: on-site terrazzo, in which workers at the construction site apply a mixture of terrazzo's raw material aggregate and cement paste to the construction area and then polish it, and factory-made terrazzo (so-called terrazzo tile), which is manufactured in a factory.
[0004] In on-site terrazzo, a mixture of crushed stone and cement paste is poured into the construction area such as floors and walls, and after hardening, the surface is polished and the aggregate is ground away to create the terrazzo structure.
[0005] On the other hand, in factory terrazzo, the above mixture is placed into a specified formwork, compressed to shape, and allowed to harden. After that, it is removed from the formwork, the backside is polished, and the crushed stone is ground away to produce terrazzo tiles.
[0006] Whether it is on-site terrazzo or factory terrazzo, when it is used by laying it on road surfaces, there is a problem that it becomes slippery when walking on it when the road surface gets wet due to rain, etc. Therefore, although terrazzo is sometimes laid indoors, on indoor floor surfaces, or on road surfaces in places covered by roofs, it has not been laid on outdoor road surfaces that will get wet when it rains.
[0007] In order to solve such problems, Japanese Patent Application Laid-Open No. 2005-139822 (Patent Document 1) discloses a terrazzo tile containing an aggregate having water absorption. The aggregate is, for example, waste roofing tiles. When such a terrazzo tile is laid on a road surface or the like, moisture is absorbed by the aggregate contained in the terrazzo tile even on rainy days, so that the amount of moisture remaining on the surface of the terrazzo tile is reduced, and as a result, slipping on the surface of the terrazzo tile when walking or the like is suitably prevented. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2005-139822 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0009] In general, terrazzo has a problem of insufficient mechanical strength, and when laid on floors or parking lots where heavy vehicles such as automobiles and large vehicles pass, the terrazzo cannot withstand the weight of the heavy vehicles and cracks or breaks. For this reason, currently, terrazzo is not laid on floors or parking lots where heavy vehicles pass, or if laid, it is damaged. Furthermore, terrazzo is required to have a certain water retention property (water absorption, water permeability, etc.), and if terrazzo has water retention property, it can absorb rainwater and prevent heavy vehicles from slipping, as described above.
[0010] Here, in the technology described in Patent Document 1, attention is focused on the absorbency of the aggregate contained in the terrazzo tile, but the mechanical strength of the terrazzo tile is unclear.
[0011] The present invention has been made to solve the above-mentioned problems, and aims to provide a terrazzo structure and a method for manufacturing a terrazzo structure that has sufficient mechanical strength and water retention and can be used on floors and parking lots where heavy vehicles pass by. [Means for solving the problem]
[0012] The terrazzo structure of the present invention comprises 10%-30% by weight of cement based on the total terrazzo structure, crushed sand or tiles having an average particle size within the range of 0.1mm-3.0mm and 25%-55% by weight of a binder based on the total terrazzo structure, crushed tiles or bricks having an average particle size within the range of 3.0mm-50.0mm and 5%-45% by weight of a first aggregate based on the total terrazzo structure, and crushed pebbles or ceramics having an average particle size within the range of 3.0mm-50.0mm and 0%-20% by weight of a second aggregate based on the total terrazzo structure.
[0013] The terrazzo structure manufacturing method of the present invention includes adding water to the additives, which are 10%-30% by weight of cement based on the total additives, crushed sand or tiles with an average particle size within the range of 0.1mm-3.0mm, and 25%-55% by weight of binder based on the total additives, crushed tiles or bricks with an average particle size within the range of 3.0mm-50.0mm, and a first aggregate, which is 5%-45% by weight based on the total additives, and crushed pebbles or pottery with an average particle size within the range of 3.0mm-50.0mm, and 0%-20% by weight based on the total additives, and filling the mixture in a specified place, curing it, and hardening the mixture, and then polishing the surface of the mixture to form a terrazzo structure. Effect of the Invention
[0014] The present invention has sufficient mechanical strength and water retention, and can be applied to floors and parking lots where heavy vehicles pass by. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a conceptual diagram of each component of the terrazzo structure according to an embodiment of the present invention and the terrazzo structure after manufacture. [Diagram 2] The components, concentrations, and performance evaluation results of Examples 1-3 and Comparative Examples 1-3. [Diagram 3] The components, concentrations, and performance evaluation results of Examples 4-10. [Figure 4] This is a photograph showing a damaged area when a conventional terrazzo structure that does not contain a binder is laid in the form of tiles. [Diagram 5] 1 is a photograph showing a state in which the terrazzo structure of the present invention is laid in the form of tiles without any broken parts. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described with reference to the accompanying drawings to facilitate understanding of the present invention. Note that the following embodiment is an example of the present invention and is not intended to limit the technical scope of the present invention.
[0017] The inventors have been conducting intensive research into terrazzo structures for many years, and have surprisingly discovered that by forming the following components, a delicate balance between the cement, binder, first aggregate with good water absorption, and second aggregate with no water absorption can be achieved to bring out mechanical strength and improve water retention, and have completed the present invention based on the examples described below.
[0018] That is, the terrazzo structure according to the present invention comprises, as shown in Fig. 1, 10%-25% by weight of cement in the whole terrazzo structure, 25%-55% by weight of binder material in the whole terrazzo structure, 5%-45% by weight of first aggregate material in the whole terrazzo structure, 3.0mm-50.0mm by weight of crushed tiles or bricks, and 0%-20% by weight of second aggregate material in the whole terrazzo structure, 3.0mm-50.0mm by weight of crushed pebbles or pottery. This provides sufficient mechanical strength and water retention, making it possible to apply the structure to floors and parking lots where heavy vehicles pass.
[0019] That is, conventional terrazzo structures and terrazzo tiles are mainly composed of two types of materials, cement and aggregates that may or may not have water absorption, but these components have problems such as poor mechanical strength because they are made of different materials and have different sizes. Also, depending on the type of aggregate, there is a problem that the water retention is not possible or is insufficient.
[0020] In the present invention, by adding a binder having a size intermediate between the cement and aggregate in addition to the cement and aggregate, the cement and aggregate can be properly mixed together, thereby improving the mechanical strength.
[0021] Furthermore, in the present invention, crushed tiles or crushed bricks, which are materials with good water absorption, are used as the first aggregate, and crushed pebbles or ceramics, which are materials with poor water absorption, are used as the second aggregate. By using the first aggregate with good water absorption, the water retention of the terrazzo structure is improved, and when it is used for repairing floors or parking lots, it becomes possible to prevent puddles from forming due to rain, etc., and to prevent heavy vehicles from slipping, etc. By using the second aggregate with poor water absorption, it becomes possible to improve the mechanical strength of the terrazzo structure and strengthen its resistance to heavy objects.
[0022] Furthermore, by changing the type of aggregate, the aesthetic design of the terrazzo structure can be varied in a wide variety of ways, thereby improving the aesthetic value of the terrazzo structure.
[0023] Here, the cement is not particularly limited, but examples thereof include Portland cements such as ordinary Portland cement and high-early-strength Portland cement, and mixed cements containing mixtures of blast furnace slag, fly ash, and the like.
[0024] Also, the cement concentration is preferably within the range of 10% by weight to 30% by weight of the entire terrazzo structure, and more preferably within the range of 16% by weight to 25% by weight of the entire terrazzo structure.
[0025] Furthermore, the binder is not particularly limited as long as it is sand or crushed tile, but when the binder is sand, examples of the binder include mountain sand, river sand, silica sand, etc. When the binder is crushed tile, examples of the binder include crushed tiles collected as waste materials. Regardless of water absorption, the binder can firmly adhere the cement and aggregate as long as it is of an intermediate size between the cement and aggregate.
[0026] The average particle size of the binder is preferably within the range of 0.1 mm to 3.0 mm, and more preferably within the range of 1.0 mm to 3.0 mm.
[0027] Also, the concentration of the binder is preferably within the range of 25% to 55% by weight of the entire terrazzo structure, and more preferably within the range of 30% to 45% by weight of the entire terrazzo structure.
[0028] The first aggregate is not particularly limited as long as it is a water-absorbent material such as tiles or bricks, but if the first aggregate is tiles, for example, crushed tiles collected as waste materials can be used, as with the binder material. If the first aggregate is brick, for example, crushed bricks collected as waste materials can be used. The first aggregate may be shells or the like that have water absorbency.
[0029] The average particle size of the first aggregate is preferably within the range of 3.0 mm to 50.0 mm, and more preferably within the range of 3.0 mm to 30.0 mm.
[0030] Also, the concentration of the first aggregate is preferably within the range of 5% by weight to 45% by weight with respect to the entire terrazzo structure, and more preferably within the range of 10% by weight to 40% by weight with respect to the entire terrazzo structure.
[0031] The second aggregate is not particularly limited as long as it is a material that does not absorb water and is pebbles or crushed ceramics, but if the second aggregate is pebbles, examples of the second aggregate include crushed mountain pebbles, river pebbles, and crushed artificial marble. If the second aggregate is crushed ceramics, examples of the second aggregate include crushed ceramics collected as waste materials. The second aggregate may be glass or the like that does not absorb water.
[0032] The average particle size of the second aggregate is preferably within the range of 3.0 mm to 50.0 mm, and more preferably within the range of 3.0 mm to 30.0 mm.
[0033] Moreover, the concentration of the second aggregate is preferably within the range of 0% to 20% by weight with respect to the entire terrazzo structure, and more preferably within the range of 0% to 10% by weight with respect to the entire terrazzo structure.
[0034] The mixing ratio of the first aggregate to the second aggregate is preferably within the range of 1:0.0-4.0, more preferably within the range of 1:0.0-3.0, and even more preferably within the range of 1:0.0-2.0, in terms of weight ratio (weight concentration ratio). In particular, when the mixing ratio of the first aggregate is high, the water retention of the entire terrazzo structure is improved.
[0035] In addition, the mixing ratio of the binder to the total aggregate (total concentration by weight) consisting of the first aggregate and the second aggregate is preferably within the range of 1:0.2-3.0, more preferably within the range of 1:0.6-2.5, and even more preferably within the range of 1:0.6-2.0, in weight ratio (concentration ratio by weight).
[0036] In addition, the mixing ratio of cement to the total aggregate (total concentration by weight) consisting of the first aggregate and the second aggregate is preferably within the range of 1:0.5-3.0, more preferably within the range of 1:1.0-2.5, and even more preferably within the range of 1:1.6-2.0, in weight ratio (concentration ratio by weight).
[0037] In addition, color powder may be added to impart a desired color to the terrazzo structure, a water reducing agent may be added to efficiently harden the cement, and an admixture may be added to improve compatibility with the cement.
[0038] Furthermore, the method for producing the terrazzo structure according to the present invention is not particularly limited, and for example, the above-mentioned components of the terrazzo structure may be mixed in various concentrations and cured.
[0039] Specifically, the method for manufacturing the terrazzo structure according to the present invention is to add water to the additives, which are 10%-30% by weight of cement based on the total additives, crushed sand or tiles with an average particle size within the range of 0.1mm-3mm, 25%-55% by weight of binder based on the total additives, crushed tiles or bricks with an average particle size within the range of 3.0mm-50.0mm, and 5%-45% by weight of first aggregate based on the total additives, crushed pebbles or ceramics with an average particle size within the range of 3.0mm-50.0mm, and 0%-20% by weight of second aggregate based on the total additives, and fill the mixture in a specified place where the terrazzo structure is to be laid, cure it, and harden the mixture, and then polish the surface of the mixture to form the terrazzo structure.
[0040] Here, the surface of the terrazzo structure after polishing may be subjected to a shot blasting treatment or the like to provide irregularities on the surface of the terrazzo structure, thereby imparting anti-slip properties.
[0041] The terrazzo structure according to the present invention can be applied to on-site terrazzo constructed on-site, or factory terrazzo produced by tile manufacturing. EXAMPLES
[0042] Examples and comparative examples of the present invention will be described below in detail, but the application of the present invention is not limited to these examples. (Manufacturing of terrazzo structures)
[0043] As shown in Figures 2 and 3, the components were mixed to produce terrazzo structures of Examples 1 to 11 and Comparative Examples 1 to 3. The values in the tables indicate the concentration by weight (% by weight). Example 1
[0044] As shown in FIG. 1, the cement concentration was set to 18.9% by weight, sand with an average particle size of 0.1-3 mm was used as the binder with a concentration of 38.8% by weight, crushed tiles with an average particle size of 3.0-50.0 mm was used as the first aggregate with a concentration of 26.9% by weight, and pebbles with an average particle size of 3.0-50.0 mm was used as the second aggregate with a concentration of 15.4% by weight. These were placed in a specified container, water was added appropriately, and mixed to create a mixture. The mixture was then filled into a specified formwork, cured, and the water was removed, and a terrazzo structure was manufactured as Example 1. Example 2
[0045] A terrazzo structure was manufactured under the same conditions as in Example 1, except that the binder in Example 1 was changed from sand to crushed tiles with an average particle size in the range of 0.1 mm to 3.0 mm, the first aggregate was changed from crushed tiles to crushed bricks with an average particle size in the range of 3.0 mm to 50.0 mm, and the second aggregate was changed from pebbles to crushed ceramics with an average particle size in the range of 3.0 mm to 50.0 mm. This was designated Example 2. Example 3
[0046] A terrazzo structure was manufactured under the same conditions as in Example 1, except that the binder in Example 1 was changed from sand to crushed roof tile with an average particle size in the range of 0.1 mm to 3.0 mm. This was designated Example 3. Comparative Example 1
[0047] A terrazzo structure was manufactured under the same conditions as in Example 1, except that the binder was omitted, the concentration of the first aggregate was changed from 26.9% by weight to 46.9% by weight, and the concentration of the second aggregate was changed from 15.4% by weight to 34.2% by weight, and this was designated Comparative Example 1. Comparative Example 2
[0048] A terrazzo structure was manufactured under the same conditions as in Example 1, except that the binder was omitted, the cement concentration was changed from 18.9% by weight to 40.0% by weight, the concentration of the first aggregate was changed from 26.9% by weight to 50.0% by weight, and the concentration of the second aggregate was changed from 15.4% by weight to 10.0% by weight, and this was designated Comparative Example 2. Comparative Example 3
[0049] A terrazzo structure was manufactured under the same conditions as in Example 1, except that the binder was omitted, the cement concentration was changed from 18.9% by weight to 30.0% by weight, the first aggregate was changed from crushed roof tiles to crushed bricks having an average particle size in the range of 3.0mm-50.0mm, the concentration of the first aggregate was changed from 26.9% by weight to 30.0% by weight, the second aggregate was changed from pebbles to crushed ceramics having an average particle size in the range of 3.0mm-50.0mm, and the concentration of the second aggregate was changed from 15.4% by weight to 40.0% by weight. This was designated Comparative Example 3. Example 4
[0050] As shown in FIG. 3, a terrazzo structure was manufactured under the same conditions as in Example 1, except that the cement concentration in Example 1 was changed from 18.9% by weight to 24.0% by weight, the binder concentration was changed from 38.8% by weight to 45.0% by weight, the first aggregate concentration was changed from 26.9% by weight to 25.0% by weight, and the second aggregate concentration was changed from 15.4% by weight to 6.0% by weight. This was designated Example 4. Example 5
[0051] A terrazzo structure was manufactured under the same conditions as in Example 1, except that the cement concentration in Example 1 was changed from 18.9% by weight to 25.0% by weight, the binder concentration was changed from 38.8% by weight to 25.0% by weight, the first aggregate concentration was changed from 26.9% by weight to 30.0% by weight, and the second aggregate concentration was changed from 15.4% by weight to 20.0% by weight. This was designated Example 5. Example 6
[0052] A terrazzo structure was manufactured under the same conditions as in Example 1, except that the cement concentration in Example 1 was changed from 18.9% by weight to 15.0% by weight, the binder concentration was changed from 38.8% by weight to 55.0% by weight, the first aggregate concentration was changed from 26.9% by weight to 20.0% by weight, and the second aggregate concentration was changed from 15.4% by weight to 10.0% by weight. This was designated Example 6. Example 7
[0053] A terrazzo structure was manufactured under the same conditions as in Example 1, except that the cement concentration in Example 1 was changed from 18.9% by weight to 29.0% by weight, the binder concentration was changed from 38.8% by weight to 45.0% by weight, the first aggregate concentration was changed from 26.9% by weight to 6.0% by weight, and the second aggregate concentration was changed from 15.4% by weight to 20.0% by weight. This was designated Example 7. Example 8
[0054] A terrazzo structure was manufactured under the same conditions as in Example 1, except that the cement concentration in Example 1 was changed from 18.9% by weight to 20.0% by weight, the binder concentration was changed from 38.8% by weight to 35.0% by weight, the first aggregate concentration was changed from 26.9% by weight to 45.0% by weight, and the second aggregate was eliminated. This was designated Example 8. Example 9
[0055] A terrazzo structure was manufactured under the same conditions as in Example 1, except that the cement concentration in Example 1 was changed from 18.9% by weight to 20.0% by weight, the binder was changed from sand to crushed tiles with an average particle size in the range of 0.1mm-3.0mm, the binder concentration was changed from 38.8% by weight to 40.0% by weight, the first aggregate concentration was changed from 26.9% by weight to 30.0% by weight, and the second aggregate concentration was changed from 15.4% by weight to 10.0% by weight. This was designated Example 9. Example 10
[0056] A terrazzo structure was manufactured under the same conditions as in Example 1, except that the cement concentration was changed from 18.9% by weight to 20.0% by weight, the binder was changed from sand to crushed tiles with an average particle size in the range of 0.1mm-3.0mm, the binder concentration was changed from 38.8% by weight to 40.0% by weight, the first aggregate was changed from crushed tiles to crushed bricks with an average particle size in the range of 3.0mm-50.0mm, the concentration of the first aggregate was changed from 26.9% by weight to 30.0% by weight, the second aggregate was changed from pebbles to crushed ceramics, and the concentration of the second aggregate was changed from 15.4% by weight to 10.0% by weight. This was designated as Example 10. (Evaluation method)
[0057] Next, the performance of the terrazzo structure after fabrication was evaluated. The performance evaluation items were (1) mechanical strength and (2) water retention. (1) Mechanical strength
[0058] The mechanical strength was measured by filling a cylindrical frame with uncured terrazzo structure and using it as a cylindrical terrazzo structure specimen. The specimen was compressed until it broke, and the strength at break (N / mm 2 ) was measured to measure the mechanical strength.
[0059] The evaluation conditions were slump 15.5cm, slump flow 29.0cm x 28.0cm, and air content 6.0%. The mechanical strength of the terrazzo structure was evaluated according to the following evaluation criteria. A rating of "Good" indicates that the product is acceptable. (standard)
[0060] ○: Mechanical strength is 18N / mm 2 If this is the case, the mechanical strength is sufficient to withstand heavy vehicles. ×: Mechanical strength is 18N / mm 2 If it is less than this, the mechanical strength is not sufficient to withstand the load of a heavy vehicle. (2) Water retention
[0061] The water retention was measured by the following procedure. First, the manufactured terrazzo structure was dried, and the weight (kg) of the dried terrazzo structure was measured as the dry weight. Next, the dried terrazzo structure was immersed in water for 24 hours. After that, the terrazzo structure was taken out of the water and left in an enclosed space for 30 minutes, and the weight (kg) of the terrazzo structure after being left was measured as the water-retained weight. The water retention rate (%) was calculated by {water-retained weight (kg)-dry weight (kg)} / dry weight (kg)*100.
[0062] The terrazzo structure was evaluated according to the following criteria to see whether it had sufficient water retention. A rating of "good" indicates that the product passed the test. (standard)
[0063] ○: If the water retention rate is 10% or more, the surface has enough water retention to prevent heavy vehicles from slipping. ×: If the water retention rate is less than 10%, the water retention is such that a heavy vehicle would slip. (Evaluation Results)
[0064] As shown in Figure 2, in Comparative Example 1-3, which does not have a binder, the evaluation results for both mechanical strength and water retention were "X". Thus, in the evaluation results of Comparative Example 1-3, neither mechanical strength nor water retention was guaranteed, and since there was an "X" in the results, it was an unsuccessful product.
[0065] On the other hand, in Example 1-3 containing a binder, the evaluation result of the mechanical strength was "good" and the evaluation result of the water retention was "good", and the product was acceptable.
[0066] Furthermore, as shown in FIG. 3, in Example 4-10 in which the cement concentration was changed, the binder concentration was changed, the first aggregate concentration was changed, or the second aggregate concentration was changed, the evaluation result of the mechanical strength was “◯”, and the product was acceptable.
[0067] Furthermore, in the case of conventional terrazzo structures without connecting materials, as shown in Figure 4, when a terrazzo structure is laid in the form of tiles in a parking lot where heavy vehicles pass through, it cannot withstand the weight of the heavy vehicles and the edges of the tiles are damaged.
[0068] On the other hand, as shown in Fig. 5, when the terrazzo structure of the present invention (Example 1) was laid in a tile-like manner in a parking lot where heavy vehicles pass, it was able to fully withstand the weight of the heavy vehicles. In Fig. 5, heavy vehicles such as buses pass through, but the terrazzo structure remains intact without being damaged. In addition, because the terrazzo structure has water retention, heavy vehicles can pass through without problems even on rainy days. [Industrial Applicability]
[0069] As described above, the terrazzo structure and the manufacturing method for the terrazzo structure according to the present invention are useful for all buildings that require mechanical strength, including floors and parking lots over which heavy vehicles pass, and are effective as terrazzo structures and manufacturing methods for terrazzo structures that have sufficient mechanical strength and water retention and can be applied to floors and parking lots over which heavy vehicles pass.
Claims
1. 10% to 30% by weight of cement based on the total terrazzo structure; A binder made of crushed sand or tiles, the average particle size of which is within the range of 0.1 mm to 3.0 mm, and the binder is 25% to 55% by weight of the entire terrazzo structure; A first aggregate, which is crushed tile or brick and has an average particle size within the range of 3.0 mm to 50.0 mm, and is 5% by weight to 45% by weight of the entire terrazzo structure; A second aggregate is a crushed material of pebbles or ceramics having an average particle size in the range of 3.0 mm to 50.0 mm, and is 0% to 20% by weight of the total terrazzo structure; A terrazzo structure comprising:
2. The mixing ratio of the first aggregate to the second aggregate is within the range of 1:0.0-4.0 by weight. The terrazzo structure according to claim 1.
3. The mixing ratio of the binder to the total aggregate of the first aggregate and the second aggregate is within the range of 1:0.2-3.0 by weight. The terrazzo structure according to claim 1 or 2.
4. 10%-30% by weight of cement based on total additives; A binder of crushed sand or tiles having an average particle size in the range of 0.1 mm to 3.0 mm, and 25% to 55% by weight of the total additives; A first aggregate which is crushed tile or brick and has an average particle size within the range of 3.0 mm to 50.0 mm, and is 5% by weight to 45% by weight of the total additives; A second aggregate, which is a crushed pebble or ceramic material and has an average particle size within the range of 3.0 mm to 50.0 mm, and is 0% to 20% by weight of the total additives; Add water to the additive and fill the mixture in a specified place, cure it, and harden the mixture. Then, polish the surface of the mixture to make a terrazzo structure. A method for manufacturing terrazzo structures.
Citation Information
Patent Citations
Terrazzo tile
JP2005139822A